BODY SATISFACTION AND INCIDENCE OF PHYSICAL EXERCISE PRACTICES BETWEEN PHYSICAL EDUCATION TEACHERS WORKING IN HEALTH CLUBS (Fiep Bulletin - online, 2013)
This study aimed to investigate the satisfaction with body weight, height, and BMI of physical education teachers working in two academies of gymnastics and bodybuilding in the municipalities of Teresópolis/RJ, and in a of Juiz de Fora/MG, by the difference between the average body weight and height current self-reported and idealized, serving these variables for the calculation of current BMI and idealized. To check the incidence among these professionals that adopt a routine of physical exercises focused on own body aesthetic and physical conditioning. These data indicate that possibly the satisfaction with the body weight between the individuals of the sample may result in high incidence of professionals who practice physical exercises routinely.
Keywords: Physical Education Teacher; body satisfaction; workout routine